1,3,2,5-Diazadiborinine featuring nucleophilic and electrophilic boron centres - Wu, Di (2015)
The seminal discovery in 1865 by Kekulé that benzene nucleus exists with cyclic skeleton is considered to be the beginning of aromatic chemistry. Since then, a myriad of cyclic molecules displaying aromatic property have been synthesized. Meanwhile, borazine (B3N3H6), despite the isostructural and isoelectronic relationships with benzene, exhibits little aromaticity. Herein, we report the synthesis of a 1,3,2,5-diazadiborinine (B2C2N2R6) derivative, a hybrid inorganic/organic benzene, and we present experimental and computational evidence for its aromaticity. In marked contrast to the reactivity of benzene, borazine, and even azaborinines previously reported, 1,3,2,5-diazadiborinine readily forms the adducts with methyl trifluoromethanesulfonate and phenylacetylene without any catalysts. Moreover, 1,3,2,5-diazadiborine activates carbon dioxide giving rise to a bicycle[2,2,2] product, and the binding process was found to be reversible. These results, thus, demonstrate that 1,3,2,5-diazadiborinine features both nucleophilic and electrophilic boron centres, with a formal B(+I)/B(+III) mixed valence system, in the aromatic six-membered B2C2N2 ring.